Tuning the mitochondrial rotary motor with light - Sommer, Andrei P. (Ann Transl Med, 2015)
Skin surface temperature has been proposed as an in vivo clinical biomarker for monitoring the detrimental effect of biostimulatory laser applications. In some cases, such as wound healing and cosmetic applications, the target of the irradiation is the skin surface. In other cases, the light has to reach deeper tissues, for instance, during the irradiation of internal body organs. Prerequisite for reproducible biostimulatory effects is that the light intensity surpasses a minimum threshold. Because of the loss of light intensity caused by absorption and scattering, targeting deeper tissues always implies that the intensity at the skin surface will be much higher than that at the target site. Derived from laboratory experiments which showed that virtually the same light which produces biostimulatory effects in cells in vitro and tissues in vivo is instrumental in reducing the viscous friction in nanoconfined systems, we arrive to a new understanding of the effect of biostimulatory levels of light on mitochondria. One immediate result is insight into strategies which promise to maximize the biostimulatory effect and minimize potential phototoxic effects during treatment of deeper tissues. Such optimization strategies are also promising for experimental and therapeutic in vitro applications, in particular in combination with cell-friendly microenvironments.